2004
DOI: 10.1029/2003je002088
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic signatures of dust devils from the 2000–2001 MATADOR desert tests

Abstract: Dust devils are significant meteorological phenomena on Mars: They are ubiquitous, continually gardening the Martian surface, and may be the primary atmospheric dust‐loading mechanism in nonstorm seasons. Further, dust grains in the swirling dust devils may become electrically charged via triboelectric effects. Electrical effects associated with terrestrial dust devils have been reported previously, but these were isolated measurements (electric fields only) with no corroborating measurements. To study the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
118
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 31 publications
8
118
0
Order By: Relevance
“…The time evolution of space charge density is very similar to the initial accumulation of the thunderstorm space charge in the QE heating model before a conventional breakdown is reached [Pasko et al, 1997]. This maximum electric field for a typical terrestrial dust devil is difficult to compare with experimental measurements, all of which have strongly saturated at a few kV/m [Freier, 1960;Crozier, 1964Crozier, , 1970Farrell et al, 2004], but the predicted value of 150 kV/m is not inconsistent with these measurements. Very recently, Jackson and Farrell (submitted man- Melnik and Parrot [1998], the dissipation of dust grain charge due to atmospheric conductivity is fully considered in our FE simulation.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 73%
See 4 more Smart Citations
“…The time evolution of space charge density is very similar to the initial accumulation of the thunderstorm space charge in the QE heating model before a conventional breakdown is reached [Pasko et al, 1997]. This maximum electric field for a typical terrestrial dust devil is difficult to compare with experimental measurements, all of which have strongly saturated at a few kV/m [Freier, 1960;Crozier, 1964Crozier, , 1970Farrell et al, 2004], but the predicted value of 150 kV/m is not inconsistent with these measurements. Very recently, Jackson and Farrell (submitted man- Melnik and Parrot [1998], the dissipation of dust grain charge due to atmospheric conductivity is fully considered in our FE simulation.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 73%
“…The modeled terrestrial dust devil electric field reaches breakdown value (3 MV/m) in less than 5 min. This model predicts unlimited growth of dust devil electric fields that are not consistent with past observations of terrestrial dust devils, where only a maximum electric field of a few kV/m has been observed [Crozier, 1970;Farrell et al, 2004]. Most recently, Jackson and Farrell (submitted manuscript, 2005) measured near 120 kV/m QE fields of dust devils with a carefully calibrated electrometer.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations